Quelques problèmes de l’emploi d’émetteurs gamma à basse énergie pour la scintigraphie - Krasznai, I.; Földes, J.; Takacs, Mrs I. (Nuklearmedizin - NuclearMedicine, 1969)
Two problems of using low-energy gamma rays for scanning are discussed:1. Model experiments to determine the effect of environmental conditions (tissue scattering) on the quality of scans are described. The scattering is found to affect the quality only for scanners without background subtraction (e.g. spark chambers) because the scattered radiation is not in excess of 5 to 7%, i.e. it is less than the general level of background subtraction (10 to 15%, minimum).2. Calculations are made to evaluate the applicability of various isotopes (from 28 to 412 keV) to the detection of inactive areas at various depths in thick organs. The optimum energy is found to range from 70 to 150 keV. It is suggested to scan such areas by a new method based on the simultaneous administration of two isotopes. The initial results of this energy-selective isotopic tomography obtained by phantom experiments with 125I and 131I are also presented.